2020
DOI: 10.48550/arxiv.2012.14016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Approximate gauge independence of the induced gravitational wave spectrum

Guillem Domènech,
Misao Sasaki

Abstract: Gravitational waves (GWs) induced by scalar curvature fluctuations are an important source of the cosmological GW background and a crucial counterpart of the primordial black hole scenario. However, doubts have been cast on the theoretically predicted induced GW spectrum due to its seeming gauge dependence. In this paper, we shed light on the gauge dependence issue of the induced GW spectrum in general cosmological backgrounds. First, inspired by the Hamiltonian formalism we provide very simple formulas for th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…In practice, it may not be feasible to find the analytic form of χ h , the gauge condition, but the choice of χ h (the zero-IGW gauge) satisfying the above relation makes the IGW h ij in that gauge vanishes. This does not imply that the IGW can be "gauged away" as mentioned in [22]; h ijχ is the same as h ij in the zero-shear gauge and indicates a gauge-invariant combination, thus cannot be gauged away. It merely reflects that the IGW is gauge-dependent, and therefore we can find the gauge condition where the IGW vanishes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In practice, it may not be feasible to find the analytic form of χ h , the gauge condition, but the choice of χ h (the zero-IGW gauge) satisfying the above relation makes the IGW h ij in that gauge vanishes. This does not imply that the IGW can be "gauged away" as mentioned in [22]; h ijχ is the same as h ij in the zero-shear gauge and indicates a gauge-invariant combination, thus cannot be gauged away. It merely reflects that the IGW is gauge-dependent, and therefore we can find the gauge condition where the IGW vanishes.…”
Section: Discussionmentioning
confidence: 97%
“…Most recently, Ref. [22] preferred the Poisson gauge based on the coincidence among some gauges far inside the horizon for nonvanishing pressure. However, this mathematical observation alone cannot replace physical justification for a particular gauge choice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found the new gauge invariant second-order GWs converged and were identical with the one in Newton gauge [179]. The idea of constructing new observable quantities was also tried in [180], where the authors found, for a series of gauges where the source term decay at a late time, the energy density of SIGWs will be identical with that in Newton gauge.…”
Section: Gauge Issue Of Scalar Induced Gravitational Wavesmentioning
confidence: 96%
“…It is well known that at first order in perturbation theory the scalar and tensor perturbations are decoupled, however, at second order the free wave equation of tensor perturbations gets a source term of scalar perturbations. Thus, when the scalar perturbations reenter the Hubble radius in the radiation-dominated(RD) era, it can leads to the production of secondorder GWs [8,9], and if the power spectrum of scalar perturbations is enhanced at small scales, the induced GWs can be sizable to be detected by experiments in near future [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%